Transformation der räumlichen Planung durch Ökosystemleistungen? Einschätzungen und Erfahrungen zu den Potenzialen aus ausgewählten Forschungsvorhaben - Hansen, Rieke; Dehnhardt, Alexandra; Marzelli, Stefan (Raumforschung und Raumordnung | Spatial Research and Planning, 2022)
To counteract the effects of climate change and biodiversity loss, sustainable transformations of societal systems and processes, as well as spatial planning, are required. Ecosystem services are considered as a concept that could transform the management of natural resources towards more sustainability. On the basis of six application-oriented research projects, this paper analyses the extent to which transformation has played a role in planning-related research on ecosystem services so far and what potential experts see for contributing to transformative change in the context of spatial planning by means of ecosystem services. The current research projects on ecosystem services predominantly do not directly refer to transformative processes and strive for changes within the existing planning framework. However, if research would be designed accordingly, it would be possible to contribute to transformative processes. Among other things, the concept of ecosystem services can be used to promote system thinking, cross sectorial boundaries, or involve civic stakeholders to a greater extent. Experiments in research could be the basis for transforming the planning system starting at the niche level.
Keywords: Ecosystem services; Transformation; Governance; Transdisciplinarity; Stakeholder; Biodiversity